Physical Rehabilitation in the System of Remedial Treatment of Patients after COVID-19: a Review - Maria S. Petrova; Maya A. Khan; Natalya A. Mikitchenko (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2023)
INTRODUCTION. The global spread of the new coronavirus infection COVID-19 determines the relevance of studying the clinicalfeatures and long-term consequences of the disease in children. Respiratory tract lesions in COVID-19 are the most common symptomsin the pediatric population. At the same time, the possibility of the development of gastrointestinal, neurological and psychologicaldisorders has now been established, which is important to consider when designing medical rehabilitation programs for such patients.RESULTS AND DISCUSSION. The article describes modern approaches to the organization of 3-stage medical rehabilitation of patientswho have undergone a new coronavirus infection COVID-19. Medical rehabilitation of such patients is aimed at restoring the ventilationfunction of the lungs, improving bronchial patency and drainage function of the respiratory tract, normalizing the functional state ofthe cardiovascular system, gastrointestinal tract, muscle tone, increasing exercise tolerance and the defenses of the child's body. Themost important component of rehabilitation measures, in addition to drug therapy and physiotherapy methods carried out for suchpatients, is physical rehabilitation, that is, the use of physical exercises for therapeutic, preventive and rehabilitative purposes. Theauthors describe the main tasks, means and forms of physical therapy, motor modes and intensity of load for each stage of medicalrehabilitation, the principles of a differentiated approach to the selection of basic physical rehabilitation measures taking into accountthe target organ, the stage of medical rehabilitation are presented.CONCLUSION. Physical rehabilitation is a mandatory component of the individual medical rehabilitation program for children whohave suffered COVID-19. The differentiated application of physical rehabilitation, taking into account the target organ, the severityof the disease, the stage of medical rehabilitation, makes it possible to achieve an earlier and complete restoration of the impairedfunctions of various organs and systems.